Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T20:50:20+01:00
A)16-2x-27+3x=0
11+x=0
x=-11
b) -3x-1+5x-2=1
2x-3=1
2x=-2
x=-1
c)3x-6-5x=10
-2x-6=10
-2x=16
x=-8
d)4x-5-2x-6=-4
2x-11=-4
2x=7
x=3,5
  • Użytkownik Zadane
2010-02-16T20:51:45+01:00
A x = 11
b x = 2
c x = -8
d x = 3,5
2010-02-16T20:54:29+01:00
A)2(8-x)-3(9-x)=0
16-2x-27+3x=0
-2x+3x=-16+27
x=11/1
x=11


b)-(3x+1)+5x-2=1
-3x-1+5x-2=1
-3x+5x=1+2+1
2x=4/2
x=2


c)3(x-2)-5x=10
3x-6-5x=10
3x-5x=10+6
-2x=16/-2
x=-8


d)(4x-5)-2(x+3)=-4
4x-5-2x-6=-4
4x-2x=-4+6+5
2x=7/2
x=3.5


mam nadzieje , że pomogłam;]]